MEWUJUDKAN MASYARAKAT TANGGUH BENCANA MELALUI PEMBERDAYAAN KELOMPOK PEMUDA LIMAU MA TUBU BERBASIS KOMUNITAS - Bundang, Syarifullah; Tangge, Nurul Ainun; Tidore, Muh. Faedly H.; Arsdin, Dian Dwi Apriliani; Karisman, Karisman; Adrian, Darmansyah (Jurnal Pengabdian Masyarakat Khatulistiwa, 2025)
ABSTRACTIn 2011 and 2012 there was a cold lava flood eruption disaster in Ternate City and one of the areas most affected was Tubo Village which resulted in casualties, infrastructure and materials. Based on these conditions, it is necessary to provide assistance to the Tubo Village community through the Limau Ma Tubu Youth so that a disaster resilient community can be created. To achieve this goal, several activities were carried out, such as outreach on disaster mitigation, education on disaster preparedness and training on Early Warning System tools and communication tools (HT). To measure participants' initial knowledge and increase in knowledge, a Pre-Test and Post-Test were carried out with a total of 10 questions. The enthusiasm of young people was quite high in participating in this activity, this could be seen from the number of participants which reached 18 people. The implementation of activities takes place in 3 stages of activities with different implementation times. Pre-Test results related to disaster mitigation generally show a percentage value of 62,5 %, these results indicate that the level of participants' knowledge is still limited. However, after all the series of activities had been carried out, a Post-Test was carried out, showing the results showed a quite drastic increase in knowledge with a percentage value reaching 90 %.Keywords: Tubo; eruption; limau ma tubu; disaster mitigation; disaster resilientABSTRAKTahun 2011 dan 2012 telah terjadi bencana erupsi banjir lahar dingi di Kota Ternate dan salah satu daerah yang paling terdampak yaitu Kelurahan Tubo yang mengakibatkan adanya korban jiwa, infrastruktur dan materi. Berdasarkan kondisi tersebut, perlu untuk dilakukan pendampingan kepada masyarakat Kelurahan Tubo melalui Pemuda Limau Ma Tubu sehingga terwujud masyarakat Tangguh bencana. Untuk mencapai tujuan tersebut dilaksanakan beberapa kegiatan, seperti sosialisasi mitigasi bencana, penyuluhan kesiapasiagaan bencana dan pelatihan alat Early Warning System dan alat komunikasi (HT). Untuk mengukur pengetahuan awal dan peningkatan pengetahuan peserta maka dilakukan Pre-Test dan Post-Test dengan jumlah soal 10 nomor. Antusias pemuda cukup tinggi mengikuti kegiatan tersebut, hal itu terlihat dari jumlah peserta yang mencapai 18 orang. Pelaksanaan kegiatan berlangsung 3 tahapan kegiatan dengan waktu pelaksanaan yang berbeda beda. Hasil Pre-Test terkait dengan mitigasi bencana secara umum menunjukan nilai persentase sebesar 62,5 %, hasil tersebut menunjukan bahwa tingkat pengetahuan peserta masih terbatas. Namun setelah semua rangkaian kegiatan sudah dilaksanakan kemudian dilakukan Post-Test menunjukan hasil yang mengalami peningkatan pengetahuan cukup drastic dengan nilai persentase mencapai 90 %.Kata Kunci: Tubo; erupsi; pemuda limau ma tubu; mitigasi bencana; Tangguh bencana